Inguinal hernia repair: Toward Asian guidelines. Issue 1 (February 2015) - Lomanto, Davide; Cheah, Wei‐Keat; Faylona, Jose Macario; Huang, Ching Shui; Lohsiriwat, Darin; Maleachi, Andy; Yang, George Pei Cheung; Li, Michael Ka‐Wai; Tumtavitikul, Sathien; Sharma, Anil; Hartung, Rolf Ulrich; Choi, Young Bai; et al.
Abstract Groin hernias are very common, and surgical treatment is usually recommended. In fact, hernia repair is the most common surgical procedure performed worldwide. In countries such as the USA, China, and India, there may easily be over 1 million repairs every year. The need for this surgery has become an important socioeconomic problem and may affect health‐care providers, especially in aging societies. Surgical repair using mesh is recommended and widely employed in Western countries, but in many developing countries, tissue‐to‐tissue repair is still the preferred surgical procedure due to economic constraints. For these reason, the development and implementation of guidelines, consensus, or recommendations may aim to clarify issues related to best practices in inguinal hernia repair in Asia. A group of Asian experts in hernia repair gathered together to debate inguinal hernia treatments in Asia in an attempt to reach some consensus or develop recommendations on best practices in the region. The need for recommendations or guidelines was unanimously confirmed to help overcome the discrepancy in clinical practice between countries; the experts decided to focus mainly on the technical aspects of open repair, which is the most common surgery for hernia in our region. After the identification of 12 main topics for discussion (indication, age, and sex; symptomatic and asymptomatic hernia: type of hernia; type of treatment; hospital admission; preoperative care; anesthesia; surgical technique; perioperative care; postoperative care; early complications; and long‐term complications), a search of the literature was carried out according to the five levels of the Oxford Classification of Evidence and the four grades of recommendation.